The Cost of Compliance: Aligning NEPA Environmental Impact Statements with Strategic Risk Allocation and Value Engineering in High-Density Data Centre Rollouts - Suleman, Rao Shahrukh (ACADEMIA International Journal for Social Sciences, 2026)
The rapid expansion of high-density data centers, driven by artificial intelligence demands, frequently triggers the National Environmental Policy Act (NEPA). Historically, the resulting Environmental Impact Statements (EIS) imposed severe regulatory bottlenecks, leading to protracted project delays, increased litigation risks, and massive capital expenditure bleed. However, recent statutory reforms mandating strict two-year EIS completion deadlines have shifted the primary developer risk from prolonged delays to premature project rejection. To address this evolving challenge, this study employs a qualitative theoretical modeling approach to bridge the interdisciplinary gap between environmental jurisprudence and construction management. This study proposes the ’Compliance-Value-Risk’ (CVR) integration model, a predictive project delivery framework distinct from retrospective cost value reconciliation accounting. This framework leverages value engineering as a proactive technical strategy to embed sustainable technologies, such as advanced cooling architectures and renewable microgrids, into the early design phase. This satisfies strict EIS evidentiary thresholds and actively secures regulatory approvals. Simultaneously, the model applies strategic risk allocation through agile Engineering, Procurement, and Construction (EPC) contracts. By utilizing phased conditions precedent and revised force majeure clauses, this approach shields developers from the financial fallout of residual regulatory friction. Ultimately, this study demonstrates that by shifting environmental compliance from an isolated legal hurdle to a core project management function, project directors can effectively mitigate the financial and temporal costs of NEPA regulations in modern digital infrastructure rollouts.